2016
DOI: 10.1080/19443994.2015.1043489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydraulic pressure and pH on organic fouling in pressure retarded osmosis (PRO) process

Abstract: A B S T R A C TPressure retarded osmosis (PRO) is a promising membrane-based process for producing clean and renewable energy. Since the major driving force is the salinity gradient between the feed and draw solutions, PRO can operate without a large environmental footprint. However, the performance of PRO can be severely limited by fouling, with organic fouling commonly deemed the main factor influencing PRO performance, since even a small amount of organic foulants can cause a significant flux decline. In sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The study indicates that for brine-wastewater PRO to be viable, the energy intensive reverse osmosis filtration step for wastewater pretreatment needs to be eliminated. , Readily accessible demonstration results are essentially absent for Korea’s GMVP project, but field tests with actual seawater and wastewater will likely face similar fouling difficulties. Evidence from actual operational experience and laboratory studies compellingly show that impaired water sources, due to the presence of more foulants, will cause greater fouling than cleaner river water. ,,, A model-based analysis of the process noticeably did not factor in pretreatment costs and fouling impact . Furthermore, while the higher c HC achieved with membrane distillation in the GMVP project is advantageous for boosting membrane power density and specific work extraction in PRO and RED, , the added step will require substantial capital expense from additional membrane modules and also incur operating cost that can weigh unfavorably in overall cost-effectiveness.…”
Section: Salinity Energy Production With Anthropogenic Streamsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicates that for brine-wastewater PRO to be viable, the energy intensive reverse osmosis filtration step for wastewater pretreatment needs to be eliminated. , Readily accessible demonstration results are essentially absent for Korea’s GMVP project, but field tests with actual seawater and wastewater will likely face similar fouling difficulties. Evidence from actual operational experience and laboratory studies compellingly show that impaired water sources, due to the presence of more foulants, will cause greater fouling than cleaner river water. ,,, A model-based analysis of the process noticeably did not factor in pretreatment costs and fouling impact . Furthermore, while the higher c HC achieved with membrane distillation in the GMVP project is advantageous for boosting membrane power density and specific work extraction in PRO and RED, , the added step will require substantial capital expense from additional membrane modules and also incur operating cost that can weigh unfavorably in overall cost-effectiveness.…”
Section: Salinity Energy Production With Anthropogenic Streamsmentioning
confidence: 99%
“…Because of the slim margins of specific energy production with seawater–river water, pretreatment cost has pivotal influence on viability. Research on fouling-resistant membranes, membrane cleaning techniques, and fouling suppression methods thus far showed encouraging progress, ,,,,,,, , but the actual cost-effectiveness of these strategies when challenged with real waters in facility-scale systems remains to be seen, given the limited success of innovations in fouling mitigation for conventional membrane-based processes. Additionally, the challenges of mass transfer limitations, parasitic pumping cost, and unintended mixing specific to PRO, RED, and AccMix have to be addressed.…”
Section: Perspectives and Outlookmentioning
confidence: 99%
“…In 2014, the scaling caused by calcium sulfate dehydrate (gypsum) was studied by considering the hydraulic pressure, membrane orientation, and types of draw solution and its concentrations [75]. More recently, the influences of the hydraulic pressure and pH on PRO organic fouling were studied by Kim et al [76]. In addition, Kim et al [77] investigated the effect of organic, inorganic, and combined fouling and reported that the support layer was more prone to inorganic fouling, specifically calcium phosphate scaling, due to the reverse solute flux and effects of ICP.…”
Section: Membrane Fouling In Promentioning
confidence: 99%